ENTREPRENEURIAL PERSPECTIVE IN ONLINE EDUCATION: EXAMINING MARKETING TECHNIQUES AND SELECTION CHOICES IN INFORMAL LEARNING THROUGHOUT THE PANDEMIC - Sukatmadiredja, Noneng Rokayah (UNIVERSITAS NEGERI SURABAYA, 2025)
The rise of the COVID-19 pandemic curtailed outdoor activities, education included. Nevertheless, a significant number of parents chose to enroll their children in non-formal education settings. This research explored the elements that impact parental preferences when selecting non-formal education amid the health crisis. A quantitative methodology was utilized to investigate the relationship between marketing tactics and parental selections. Information was gathered from 81 parents who had received promotional material from a non-formal educational institution in Surabaya, with a total of 51 parents chosen for detailed examination. Data was acquired through surveys, and SPSS was utilized for data analysis. The findings indicated that strategies involving word-of-mouth and digital learning programs played a significant role in shaping parental decisions, both as standalone factors and combined. Despite the advancements of the digital age, traditional word-of-mouth continues to hold importance, given that kids rely heavily on their parents' choices. The innovation of this study lies in the combination of traditional marketing practices and digital learning to better support the selection of non-formal education. The results offer valuable guidance for administrators at non-formal schools to enhance their marketing approaches and elevate parental contentment.